Enhancing Sales and Customer Loyalty through Marketing Innovation and Digital Communication - Deby Rita Karundeng; Moh Afan Suyanto; Yakup Yakup (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the influence of marketing innovation and digital communication strategies on sales growth and customer loyalty among micro, small, and medium-sized enterprises (MSMEs) in Gorontalo, Indonesia. Responding to the limited region-specific research in this area, the study employs a quantitative approach using path analysis to examine direct and indirect relationships among these variables. Data were collected through structured questionnaires distributed to 117 purposively selected MSME actors actively engaged in strategic business decisions. The findings reveal that marketing innovation significantly enhances both sales growth (β = 0.58) and customer loyalty (β = 0.42), while digital communication strategies also exert significant positive effects on sales (β = 0.32) and loyalty (β = 0.32). Sales growth, in turn, directly contributes to increased customer loyalty (β = 0.24). Furthermore, both marketing innovation and digital communication strategies have indirect effects on customer loyalty through their impact on sales growth. These results emphasize the importance of adopting innovative and digital strategies to improve MSME performance in emerging regions. The study offers practical recommendations for MSME managers and policymakers seeking to strengthen competitiveness and sustainability. While the research is limited to Gorontalo and cross-sectional in nature, it lays a foundation for future longitudinal and comparative studies across regions.